Modeling water balance of dammed lakes using computer code Matlab-Simulink? = Modelowanie bilansu wodnego piętrzonych jezior za pomocą programu komputerowego Matlab-Simulink? - Błażejewski, Ryszard; Murat-Błażejewska, Sadżide; Jędrkowiak, Martyna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper presents a water balance of a flow-through, dammed lake, consisted of the following terms: surface inflow, underground inflow/outflow based on the Dupuit?s equation, precipitation on the lake surface, evaporation from water surface and outflow from the lake at which a damming weir is located.
Keywords: bilans wodny; podpiętrzone jezioro; MATLAB/Simulink; Jezioro Sławianowskie; water balance; dammed lake; Sławianowskie Lake